Ion source based on Penning discharge for production of doubly charged helium ions - V. I. Voznyi; D. P. Shulha; O. O. Drozdenko; M. I. Zakharets; E. A. Mironets; O. S. Brichenko (Âderna Fìzika ta Energetika, 2017)
The article presents the results of operation of ion source with Penning discharge developed in the IAP of NAS of Ukraine to produce doubly charged helium ions He2+ beam and to increase the energy of accelerated ions up to 3.2 MeV. This energy is necessary for ERDA channel when measuring hydrogen concentration in the structural materials used in nuclear engineering. The ion source parameters are the following: discharge voltage is 6 kV, discharge current is 0.8 - 1.2 mA, the current of singly charged helium ions He+ 24 μA, the current of doubly charged helium ions He2+ 0.5 μA.